PENERAPAN PERMAINAN NAHWU MATCHING DALAM PEMBELAJARAN ISIM ISYĀRAH - Fuadi, Abdul Hafizh Nur; Panagara, Fathi Hisyam; Izzah, Nurul; Muasssomah, Muassomah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This research was conducted to increase teachers' insight in applying the nahwu game model so that they can teach Arabic easily. This research aims to explore the implementation of Nahwu Matching game as a fun and engaging approach to teach the basic structure of isim isyarah (demonstrative pronouns) in a classroom setting. The study specifically focuses on its application in a small class of third-grade students at MI Nurul Amal. The research adopts a qualitative descriptive approach with field research method, utilizing observation, interviews, and documentation as data collection techniques. The main findings reveal that the implementation of Nahwu Matching game in the small class setting is effective and well-received by the third-grade students. The game provides an engaging learning experience, and the students' positive responses demonstrate its success. The study highlights the advantages of using this game in a small classroom, as it facilitates an interactive and enjoyable learning environment. No significant limitations were found in terms of its instructional aspects. The implications of this research suggest that teachers of Arabic language can consider incorporating game-based approaches into their instruction to enhance active and innovative learning experiences. Overall, this study provides valuable insights for educators in utilizing game-based models for teaching Arabic language in an engaging and effective manner.